A Double‐Walled Tetrahedron with AgI4 Vertices Binds Different Guests in Distinct Sites. Issue 16 (13th March 2023) - Clark, Samuel E.; Heard, Andrew W.; McTernan, Charlie T.; Ronson, Tanya K.; Rossi, Barbara; Rozhin, Petr; Marchesan, Silvia; Nitschke, Jonathan R.
Abstract: A double‐walled tetrahedral metal‐organic cage assembled in solution from silver(I), 2‐formyl‐1, 8‐naphthyridine, halide, and a threefold‐symmetric triamine. The Ag I 4 X clusters at its vertices each bring together six naphthyridine‐imine moieties, leading to a structure in which eight tritopic ligands bridge four clusters in an (Ag I 4 X)4 L8 arrangement. Four ligands form an inner set of tetrahedron walls that are surrounded by the outer four. The cage has significant interior volume, and was observed to bind anionic guests. The structure also possesses external binding clefts, located at the edges of the cage, which bound small aromatic guests. Halide ions bound to the silver clusters were observed to exchange in a well‐defined hierarchy, allowing modulation of the cavity volume. The principles uncovered here may allow for increasingly more sophisticated cages with silver‐cluster vertex architectures, with post‐assembly tuning of the interior cavity volume enabling targeted binding behavior. Abstract : Atomically precise [Ag4 X] 3+ (X=I, Br, or Cl) clusters have been incorporated at the vertices of a double‐walled tetrahedron. The cage binds guests in two distinct modes: small aromatic guests bind externally, and anionic guests bind in the central cavity. Halide ions bound to the silver clusters were observed to exchange in a well‐defined hierarchy, with a preference found for the softer halides.